Numerical study of the seismic retrofitting of masonry-Infilled RC frames with openings using TRM - Filippou, Christiana; Kyriakides, Nicholas; Chrysostomou, Christis (My University, 2023)
The seismic retrofitting of existing masonry-infilled reinforced-concrete (RC) frame buildings is one major challenge of earthquake risk mitigation. In this paper, the use of promising novel alternative composite material, namely textile reinforced mortar (TRM) for seismic retrofitting masonry-infilled RC frames with central openings is examined numerically, to the best knowledge of the authors, for the first time ever. This is achieved by performing a parametric study on a validated 2D numerical model of a three-story masonry-infilled RC frame with and without TRM considering different size of central openings. This parametric study aims to examine (i) the influence of central openings on the lateral response of masonry-infilled RC frames subjected to cyclic loading and (ii) the lateral response of the three-story masonry-infilled RC frame with central openings retrofitted with TRM under cyclic loading. From the results obtained in this study, it was concluded that TRM contributes to increase the lateral capacity, stiffness, and the dissipated energy of infilled frames with openings and at the same time provides a more ductile behavior by delaying the strength and the stiffness degradation of infilled frames due to openings and further by delaying or even preventing brittle failures that occur on infilled frames due to the presence of the opening. New stiffness reduction factors for infilled frames with openings, and for TRM-retrofitted infilled frames with openings are also proposed, which can be used with an equivalent compression strut model and with a tension tie-model as an everyday practice tool for simulating infilled frames with central openings along the diagonal of the infill wall with and without TRM. A numerical sensitivity analysis is also performed aiming to investigate the influence of (i) the TRM reinforcement ratio and (ii) the type of mortar used for binding the textile reinforcement on the lateral response of the three-story masonry-infilled RC frame retrofitted with TRM subjected to cyclic loading. This study showed that by increasing the reinforcement ratio, or by using high-strength mortars for binding the textile reinforcement, the lateral capacity of infilled frames is increased leading to a more ductile behavior, but this increase is not proportional to the increase of the reinforcement ratio or to the increase of the mechanical properties of the mortar.
Keywords: cyclic loading; masonry-infilled RC frames; openings; seismic retrofitting; textile reinforced mortar (TRM)